Self-Expression of Mechanical Engineering Students on Instagram Reels: English Self-Disclosure - Nasution, Mutia (University of Surakarta, 2025)
This study explores the self-disclosure practices of Mechanical Engineering students at Politeknik Negeri Sriwijaya through their use of English on Instagram Reels. As digital natives, these students navigate identity construction in online spaces, using English as both a communicative tool and a form of emotional distancing. The research aims to understand how and why students disclose personal content in English and how this influences their language development, emotional expression, and digital identity. Employing a qualitative case study method, data were collected through observation of Instagram Reels content and in-depth interviews with selected participants. The findings reveal that students perceive English as more neutral and emotionally safer, enabling more open expression of thoughts, struggles, and achievements. Instagram Reels also serves as a platform for self-therapy, community building, and linguistic growth. This research contributes to the understanding of digital self-performance among vocational students in non-English majors and offers insights into the intersections of language use, self-expression, and media literacy in contemporary educational contexts.